Debate and division on the British left, 1917-1964. - Murphy, J. T. (John Thomas), 1888-1965; Murphy, Molly, 1890-1964; Archive Trust of the Communist Party of Great Britain (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2020)
John Thomas (J.T.) Murphy and Molly Murphy (née Morris) were a married couple who were prominent members of the Communist Party of Great Britain (CPGB) during its formative years. J.T. was expelled from the party in 1932, while Molly resigned shortly thereafter. This collection contains J.T.’s personal and political papers, which cover a wide range of subjects, from his imprisonment in 1925 and campaign to become a Member of Parliament to his travels in post-revolutionary Russia and disagreements with the CPGB leadership. Documents detailing Molly's time as a nurse on the frontlines of the Spanish Civil War are also included. Together, these materials provide an invaluable insight into the internal debates that plagued the British and European left during the 1920s and 1930s.
Date range: 1917-1964.
Keywords: Murphy, Molly, -- 1890-1964 -- Correspondence; Murphy, J. T. -- 1888-1965 -- Correspondence; Communism -- Europe -- History -- 20th century -- Sources; Communism -- Great Britain -- History -- 20th century -- Sources